Answer :

(2 a + b + 2x)(x) = – ab

2 x^{2} + (2 a + b) x + ab = 0

We know that the solution of equation ax^{2} + bx + c = 0 is given by:

For our equation, a = 2, b = (2 a + b) and c = ab

Applying the value in the formula we get,

Now we get that, x = = –b/2 or

We have, x = = – a

So the two solutions of x are –b/2 and – a

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation